Hierarchically Nitrogen‐doped Porous Carbon‐Supported Non‐noble Metal Nanoparticles for Promoting the Selective Hydrogenation of Furfural. Issue 2 (29th December 2021) - Sun, Lu; Fan, Yafei; Chu, Jie; Zhou, Xiaojian; Zhuang, Changfu; Zou, Xiaoqin; Min, Chungang; Wang, Ying; Zhu, Guangshan
Abstract: The hydrogenation of biomass into high added‐value chemicals is an efficient way of utilization. However, supported monometallic catalytic systems still show low performance. In this study, different non‐noble metal nanoparticles (NPs) are supported on hierarchically nitrogen‐doped porous carbon (M/HNPC) with high specific surface area and used in the hydrogenation reaction of furfural (FF). The experiment results exhibited that the performance of Ni/HNPC is more superior than Fe, Co and Cu. The DFT results showed that the catalytic activity of Ni/HNPC was strongly related to the intrinsic catalytic performance of Ni metal itself. The Ni/HNPC obtains the 95.2% FF conversion and 94.8% furfuryl alcohol (FOL) selectivity under mild conditions at 110 °C and 4 h, which is mainly due to the synergistic effect between metallic Ni and HNPC support. In addition, the stability of the Ni/HNPC catalyst also has been improved because of the high specific surface area and N‐doped of HNPC support. This work provides an important reference for biomass conversion with a monometallic catalyst by controlling the metal types and supports. Abstract : M/HNPC (M=Cu, Ni, Co, Fe) samples were prepared using hierarchically nitrogen‐doped porous carbon (HNPC) with a high specific surface area as the support, and used for the selective hydrogenation of furfural (FF) to furfuryl alcohol (FOL).